IMPLEMENTATION OF ESG (ENVIRONMENTAL, SOCIAL, GOVERNANCE) PRINCIPLES IN STATE-OWNED ENTERPRISES (Marketing Journal, 2025)
This article analyzes the importance and effectiveness of implementing ESG (Environmental, Social, Governance) principles in state -owned enterprises. International practice shows that integrating environmental, social, and corporate governance standards in public enterprises enhances financial stability, public trust, and competitiveness. It is scientifically substantiated that the gradual introduction of ESG standards in Uzbekistanʼs state -owned enterprises can improve the investment climate, strengthen co rporate accountability, and ensure strategic development. The article also provides a comparative analysis of foreign experiences and proposes ways to implement ESG principles under national conditions.
Keywords: ESG; environmental sustainability; social responsibility; corporate governance; state -owned enterprises; efficiency; investment attractiveness; corporate accountability; Uzbekistanʼs economy